3-aryl-4-(3,4,5-trimethoxyphenyl)pyridines inhibit tubulin polymerisation and act as anticancer agents - Chao Wang; Yujing Zhang; Shanbo Yang; Lingyu Shi; Yutao Xiu; Yudong Wu; Hongfei Jiang (Taylor & Francis Group, 2024)
AbstractA series of cis-restricted 3-aryl-4-(3,4,5-trimethoxyphenyl)pyridines as novel tubulin polymerisation inhibitors was designed based on molecular docking. Compound 9p, exhibited potent antiproliferative activity against HeLa, MCF-7, and A549 cell lines. Mechanism studies indicated that 9p potently inhibited tubulin polymerisation and disrupted the microtubule dynamics of tubulin in HeLa cells. Moreover, 9p could cause G2/M phase cell cycle arrest and apoptosis in HeLa cells. In addition, the prediction of physicochemical properties disclosed that 9p conformed well to the Lipinski's rule of five. The initial results suggest that the 3-aryl-4-(3,4,5-trimethoxyphenyl)pyridines could serve as a promising scaffold for the development of novel anticancer drugs.